The circumstances and impact of injuries on adults with learning disabilities. (August 2014) - Finlayson, Janet; Morrison, Jillian; Skelton, Dawn Ann; Ballinger, Claire; Mantry, Dipali; Jackson, Alison; Cooper, Sally-Ann
Introduction: People with learning disabilities experience higher rates of injury compared to the general population, but little is known about the circumstances and perceived impact of these injuries on people with learning disabilities themselves. Method: Content analysis was conducted from interviews with 113 adults with learning disabilities who had at least one injury in a 12-month period. Qualitative interviews were conducted with ten adults with learning disabilities (and their carers where appropriate) who had experienced serious or frequent injury or frequent falls with or without injury in a 12-month period. Findings: The most commonly reported contributory factors for injuries and/or falls were related to physical health status (for example, epilepsy) and the environment (for example, walking/banging into furniture or stairs/steps). In terms of perceived impact, the development of fear of walking outdoors unsupported or fear of crossing a road were highlighted. The non-use and misuse of assistive technology was also highlighted as a concern. Conclusion: These findings demonstrate that occupational therapists have a key role to play in tailoring injury and fall prevention strategies and interventions for people with learning disabilities. In particular, environmental assessment and monitored use of assistive technology is important.